Stranding of Beaked Whales in Santa Cruz Province, Southern Patagonia, Argentina (1895-2023) - Iñíguez Bessega, Miguel A.; Hevia, Marta; Cipriano, Frank; Belgrano, Jimena M. I.; Failla, Mauricio; Fernández Rodríguez, Antonio Jesús; Gasparrou, Cecilia; van Helden, Anton L.; Jones, Juan; Manterola, Nicolás; Reyes Reyes, M. Vanesa; Tossenberger, Vanesa P.; et al. (Aquatic Mammals, 2025)
A total of 49 records of beaked whales stranded along approximately 900 km of coast of Santa Cruz Province, Argentina, were documented between 1895 and March 2023. These include 29 previously published and unpublished records (including one specimen re-identified through DNA analysis) and 20 new records. All of these involve at least seven species in five genera. All strandings correspond to single individuals. The most frequent species found stranded were Cuvier’s beaked whales (Ziphius cavirostris) with 14 records, followed by strap-toothed whales (Mesoplodon layardii; n = 13). Species identities were based on skull morphology, tooth morphology and position in the jaw, and morphometric measurements. Additionally, mitochondrial control region DNA was sequenced to confirm species identification for 10 individuals, although confirmation was only possible in seven individuals. This study provides the first record of Arnoux’s beaked whale and Hector’s beaked whale from Santa Cruz Province and emphasizes the importance of the Southwest Atlantic Ocean for multiple beaked whale species. The potential impacts on these whale species of changing sea surface temperatures and ocean warming are unknown 0,324 Q3 SCIE 11,0